CONTRIBUTION OF ACEHNESE SCHOLARS TO THE DEVELOPMENT OF QURANIC EXEGESIS IN INDONESIA: A STUDY OF TENGKU MUHAMMAD HASBI ASH-SHIDDIEQY AND HIS WORK "TAFSIR AN-NUUR" - Fadli, Nazar (QiST: Journal of Quran and Tafseer Studies, 2024)
This article aims to discuss Tengku Muhammad Hasbi ash-Shiddieqy, a modern scholar from the Aceh region of Indonesia, and his significant work in the field of tafsir, titled "Tafsir an-Nuur". Hasbi is known as a proficient personality in various areas of Islamic sciences. In Indonesia, his competence in Islamic fields such as fiqh, uṣul al-fiqh, tafsir, and hadith has established Tengku Muhammad Hasbi Ash-Shiddieqy as a respected figure in society. Consequently, due to his areas of expertise, he is recognized as a prolific scholar who has authored academic works such as books and articles. Tafsir an-Nuur is a four-volume tafsir book that covers the interpretation of the Quranic verses from QS. al-Fātiḥa to QS. al-Nās, divided into 30-volume. In this tafsir, Quranic verses are explained succinctly, without delving into excessive detail, focusing on elucidating the fundamental meaning of the verses. Therefore, Tafsir an-Nuur falls into the category of concise (ijmālī) tafsir. This tafsir was written in Indonesian to facilitate easier understanding of the Quran's content for Indonesians. Methodologically, this article is a study that uses source research and qualitative research methods. This article primarily aims to delve into Hasbi's biography and works. Additionally, it discusses the background of the composition of Tafsir an-Nuur, its systematic approach, sources, methods, and related topics. In this context, readers are expected to gain a better understanding of Hasbi and Tafsir an-Nuur, ultimately contributing to a more comprehensive grasp of the development of tafsir studies in Indonesia.